Biomimetic Hydrogels to Promote Wound Healing - Fan, Fei; Saha, Sanjoy; Hanjaya-Putra, Donny (Frontiers in Bioengineering and Biotechnology, 2021)
Wound healing is a common physiological process which consists of a sequence of molecular and cellular events that occur following the onset of a tissue lesion in order to reconstitute barrier between body and external environment. The inherent properties of hydrogels allow the damaged tissue to heal by supporting a hydrated environment which has long been explored in wound management to aid in autolytic debridement. However, chronic non-healing wounds require added therapeutic features that can be achieved by incorporation of biomolecules and supporting cells to promote faster and better healing outcomes. In recent decades, numerous hydrogels have been developed and modified to match the time scale for distinct stages of wound healing. This review will discuss the effects of various types of hydrogels on wound pathophysiology, as well as the ideal characteristics of hydrogels for wound healing, crosslinking mechanism, fabrication techniques and design considerations of hydrogel engineering. Finally, several challenges related to adopting hydrogels to promote wound healing and future perspective are discussed.